2019
DOI: 10.1016/j.msec.2018.12.134
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic and thermal investigation into the relationship between composition, secondary structure and physical characteristics of electrospun zein nanofibers

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In another study, diluted acetic acid was employed and found to result in fibers only at low water concentrations, which showed a compact and dense structure [31]. Attempts to electrospin zein in a mixture of acetic acid, ethanol and water resulted in fibers with a beads-on-fiber morphology [32]. In addition to the challenges of electrospinning zein, the fabricated fibers tend to lose their porous structure and turn into a film upon contact with water [19,20,24,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, diluted acetic acid was employed and found to result in fibers only at low water concentrations, which showed a compact and dense structure [31]. Attempts to electrospin zein in a mixture of acetic acid, ethanol and water resulted in fibers with a beads-on-fiber morphology [32]. In addition to the challenges of electrospinning zein, the fabricated fibers tend to lose their porous structure and turn into a film upon contact with water [19,20,24,33].…”
Section: Introductionmentioning
confidence: 99%
“…There is only a limited number of studies that produced fibers from zein and PEO by electrospinning, and to the best of our knowledge there are no studies on electrospinning of mixtures of zein and SA. With respect to studies focusing on zein and PEO, zein was uniaxially electrospun with PEO [30,32], and co-axially electrospun with zein as a shell and PEO as a core [47]. However, in all cases high PEO concentrations and low zein concentrations were required, to improve the electrospinning and prevent ribbon morphology from occurring.…”
Section: Introductionmentioning
confidence: 99%
“…The background spectrum was automatically subtracted from the spectra of the samples. Individual components within the spectra were estimated by second derivative and Lorentz curve fitting in the regions of 1,700–1,600 cm −1 using OriginPro 9.0 software (OriginLab, USA) 36,37 . The area under the curve of each deconvoluted band was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Individual components within the spectra were estimated by second derivative and Lorentz curve fitting in the regions of 1,700-1,600 cm À1 using OriginPro 9.0 software (OriginLab, USA). 36,37 The area under the curve of each deconvoluted band was calculated. All the deconvolutions were done with an R 2 of 0.99.…”
Section: Ftir Analyses Of Filmsmentioning
confidence: 99%
“…The methods of forming nanocarriers from zein include antisolvent (Cheng et al., 2019; Zhang et al., 2019), electrospinning (Deng, Li, Feng, Wu, & Zhang, 2019; Heydari‐Majd, Rezaeinia, Shadan, Ghorani, & Tucker, 2019; Wang, Zhao, Barker, Belton, & Craig, 2019), electrospraying (Miguel et al., 2019), supercritical antisolvent (Franco, Reverchon, & De Marco, 2019; Palazzo, Campardelli, Scognamiglio, & Reverchon, 2019), heat‐induced self‐assembly (Wang & Zhang, 2019), and evaporation induced self‐assembly (Wang, Su, Schulmerich, & Padua, 2013). Although these methods have different processes, they follow a common mechanism.…”
Section: Characteristics Of Zeinmentioning
confidence: 99%